KETERAMPILAN METAKOGNITIF PESERTA DIDIK DENGAN MENGGUNAKAN MODEL EXPERIENTIAL LEARNING PADA MATERI SISTEM PERNAPASAN MANUSIA - Fitri Fatimah; Sistiana Windyariani; Setiono Setiono (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
This study aims to determine the metacognitive skills of students using the experiential learning model on the subject of the human respiratory system. The research method used is Quasi Experiment with Non-Equivalent Control Group Design. The research population used in this research series was students at MTs Nurul Huda in the Sukabumi district, the experimental class numbered 20, and the control class had the same number, namely 20 students. Taking the two sample classes was carried out using a purposive sampling method. The research instrument used a metacognitive skills questionnaire; several tests were used, including the N-Gain, normality, homogeneity, and hypothesis testing. The results showed a difference in the mean and N-gain values of the scores obtained by the two research classes. It was shown that the experimental class had a higher average score of 86 than the control class of 76. While the N-Gain value of the experimental class was 0.33 can be categorized as moderate, and the control class 0.30 is categorized as low. Besides that, based on hypothesis testing on the independent sample t-test, it shows a 2-tailed sig value. of 0.000 which means H0 is rejected and H1 is accepted. So it can be concluded that applying the Experiential Learning model affects improving students' metacognitive skills in the subject of the human respiratory system.